2006
DOI: 10.1590/s0102-33062006000200006
|View full text |Cite
|
Sign up to set email alerts
|

Composição florística e estrutura fitossociológica de dois fragmentos de floresta de restinga no Município de Bertioga, SP, Brasil

Abstract: Palavras-chave: Floresta de restinga inundável, Floresta de restinga não inundável, fisionomia, planície litorâneaABSTRACT -(Floristic and phytosociological analysis of two fragments of restinga forest in Bertioga, São Paulo State, Brazil). A phytosociological investigation in two fragments of restinga forest (flooded and nonflooded) in Riviera de São Lourenço complex, Bertioga, São Paulo, was carried out. Each fragment in the phytosociological survey was studied using 10×10 m plots. These plots were distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
3
53

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 7 publications
2
33
3
53
Order By: Relevance
“…Proximity to human habitats can favour herbaceous species that strongly contribute in the landscape's characteristics (Halvorsen & Edvardsen 2009). Other studies in restingas of São Paulo revealed higher H' values, ranging from 3.50 to 3.70 (Guedes et al 2006). Considering woody plants and the same inclusion criterion, the restingas of Piauí presented lower H' values in comparison with other northeastern restingas (Guadalupe, Pernambuco, with 2.64 (Cantarelli 2003), Pipa, Rio Grande do Norte, with 2.76 (Almeida Jr. & Zickel, not published), Ariquindá, Pernambuco, with 2.85 (Vicente et al 2003) and Maracaípe, Pernambuco, with 3.5 (Almeida Jr. et al 2011).…”
Section: Resultsmentioning
confidence: 80%
“…Proximity to human habitats can favour herbaceous species that strongly contribute in the landscape's characteristics (Halvorsen & Edvardsen 2009). Other studies in restingas of São Paulo revealed higher H' values, ranging from 3.50 to 3.70 (Guedes et al 2006). Considering woody plants and the same inclusion criterion, the restingas of Piauí presented lower H' values in comparison with other northeastern restingas (Guadalupe, Pernambuco, with 2.64 (Cantarelli 2003), Pipa, Rio Grande do Norte, with 2.76 (Almeida Jr. & Zickel, not published), Ariquindá, Pernambuco, with 2.85 (Vicente et al 2003) and Maracaípe, Pernambuco, with 3.5 (Almeida Jr. et al 2011).…”
Section: Resultsmentioning
confidence: 80%
“…As famílias com maior número de espécies (Asteraceae, Fabaceae, Myrtaceae, Rubiaceae e Poaceae) são típicas de outras áreas de restinga dos Estados do sul do Brasil (Silva 1990, Santos et al 2012, Korte et al 2013. Entre estas famílias, Myrtaceae e Fabaceae têm elevada riqueza de espécies em áreas de restinga localizadas nas regiões sudeste, nordeste e norte do país (Oliveira-Filho & Carvalho 1993, Pereira et al 2001, Assis et al 2004, Guedes et al 2006, Almeida Jr. & Zickel 2009, Sá & Araujo 2009, Dantas et al 2010, Silva et al 2010, Almeida Jr. et al 2011, Giareta et al 2013. Estas famílias são reconhecidas como umas das principais famílias neotropicais (Gentry 1988), com grande representatividade na vertente costeira da Mata Atlântica (Salimon & Negrelle 2001) e que melhor caracterizam a flora das restingas do Brasil (Klein 1982, Araujo & Henriques 1984.…”
Section: Resultsunclassified
“…Em ambientes de restinga, o teor de matéria orgânica é o principal responsável pelo aumento da capacidade de troca catiônica que, por sua vez, contribui para a retenção de nutrientes no solo (Ruivo et al 2005, Guedes et al 2006. Desta forma, a CTC representa a capacidade de liberação de nutrientes, propiciando a manutenção da fertilidade do solo por um período prolongado (Ronquim 2010).…”
Section: Continua Tabela 4 (Continuação)unclassified
See 1 more Smart Citation
“…Southern and southeastern Restinga sites have been more intensively studied (Lacerda et al 1984;Araújo 2000;Martins et al 2008;Lima et al 2011), although Guedes et al (2006) highlighted our lack of knowledge about the floristic and phytosociological structures of restinga vegetation in São Paulo State. Most of the works produced so far have been limited to floristic and vegetational aspects, with little emphasis on environmental patterns and processes.…”
Section: Introductionmentioning
confidence: 99%